Artificial Intelligence (AI) trends in higher education learning: Bibliometric analysis - Ai Pemi Priandani; Cepi Riyana; Asep Herry Hernawan; Laksmi Dewi; Mario Emilzoli; Gema Rullyana (Curricula: Journal of Curriculum Development, 2025)
The development of artificial intelligence (AI) technology has driven significant transformations in higher education. The integration of AI in learning offers the potential to increase the effectiveness, efficiency, and personalization of data-driven learning. This study aims to conduct a comprehensive bibliometric analysis of AI research trends in higher education learning, tracing publication patterns, source distribution, geographic distribution, and emerging themes in academic literature. The study uses a quantitative descriptive method with bibliometric analysis of Scopus publication data 2018–2023. The analysis was conducted using VOSviewer to map bibliographic relationships between publications, sources, authors, countries, and keywords. The results show that AI publications in higher education have increased rapidly, especially in 2023. The dominant themes are "artificial intelligence" and "higher education", with the latest trend towards "generative AI" and "ChatGPT". Publications appear in many interdisciplinary journals of social and computer sciences, with the United States, China, Australia, and the United Kingdom dominating research contributions. The findings provide a systematic overview of the development of AI research in higher education and serve as a strategic basis for educators, researchers, and policymakers in designing effective and sustainable AI integration in higher education.   Abstrak Perkembangan teknologi kecerdasan buatan (AI) telah mendorong transformasi signifikan dalam pendidikan tinggi. Integrasi AI dalam pembelajaran menawarkan potensi peningkatan efektivitas, efisiensi, dan personalisasi pembelajaran berbasis data. Penelitian ini bertujuan melakukan analisis bibliometrik komprehensif terhadap tren penelitian AI dalam pembelajaran pendidikan tinggi, menelusuri pola publikasi, distribusi sumber, persebaran geografis, dan tema yang muncul dalam literatur akademik. Penelitian menggunakan metode deskriptif kuantitatif dengan analisis bibliometrik data publikasi Scopus 2018–2023. Analisis dilakukan menggunakan VOSviewer untuk memetakan hubungan bibliografis antara publikasi, sumber, penulis, negara, dan kata kunci. Hasil menunjukkan publikasi AI dalam pendidikan tinggi mengalami peningkatan pesat, terutama tahun 2023. Tema dominan adalah "artificial intelligence" dan "higher education", dengan tren terkini mengarah pada "generative AI" dan "ChatGPT". Publikasi banyak muncul di jurnal interdisipliner ilmu sosial dan komputer, dengan Amerika Serikat, Tiongkok, Australia, dan Inggris mendominasi kontribusi penelitian. Temuan memberikan gambaran sistematis perkembangan penelitian AI dalam pendidikan tinggi dan menjadi dasar strategis bagi pendidik, peneliti, dan pembuat kebijakan dalam merancang integrasi AI yang efektif dan berkelanjutan di perguruan tinggi. Kata Kunci: analisis bibliometrik; desain pembelajaran; kecerdasan buatan; pembelajaran; pendidikan tinggi